ANALISIS PUTUSAN HAKIM NOMOR: 284/Pdt.G/2015/PA.Prg TENTANG AHLI WARIS PENGGANTI - Rukiah Rukiah; Saidah Saidah; Asmirayanti Asmirayanti (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2017)
Abstract: The heir of the successor or commonly called mawali is the heir who died first from the heir so his position can be replaced by his son. This is as regulated in Article 185 of the Compilation of Islamic Law (KHI). The subject matter in this paper is how the judge's verdict Number: 284 / Pdt.G / 2015 / PA. Prg in determining the respective part of the successor heirs. The findings of the study indicate that (1) The position of the surrogate heirs in the Islamic inheritance system and the customary inheritance system in Pinrang Regency is no known change of system for the heirs who died prior to the heir. (2) The position of the replacement heirs in the inheritance system according to the Compilation of Islamic Law of the heirs who died prior to the heir, his position can only be replaced by his son or grandson of the heir under Article 185 paragraph (1) Compilation of Islamic Law (KHI) a change of place in inheritance applies only to a downward line of descent and so on. (3) There is a mistake by the panel of judges in deciding on the part of the heirs and the surrogate heirs in the case Number 284 / Pdt.G / 2015 / PA.Prg.